Diagnosis of CoPAN by whole exome sequencing: Waking up a sleeping tiger's eye. Issue 7 (10th May 2017) - Evers, Christina; Seitz, Angelika; Assmann, Birgit; Opladen, Thomas; Karch, Stephanie; Hinderhofer, Katrin; Granzow, Martin; Paramasivam, Nagarajan; Eils, Roland; Diessl, Nicolle; Bartram, Claus R.; Moog, Ute
Abstract : Neurodegeneration with brain iron accumulation (NBIA) is a group of neurodegenerative disorders characterized by iron accumulation in the basal ganglia. Recently, mutations in CoA synthase ( COASY ) have been identified as a cause of a novel NBIA subtype (COASY Protein‐Associated Neurodegeneration, CoPAN) in two patients with dystonic paraparesis, parkinsonian features, cognitive impairment, behavior abnormalities, and axonal neuropathy. COASY encodes an enzyme required for Coenzyme A (CoA) biosynthesis. Using whole exome sequencing (WES) we identified compound heterozygous COASY mutations in two siblings with intellectual disability, ataxic gait, progressive spasticity, and obsessive‐compulsive behavior. The "eye‐of‐the tiger‐sign, " a characteristic hypointense spot within the hyperintense globi pallidi on MRI found in the most common subtype of NBIA (Pantothenate Kinase‐Associated Neurodegeneration, PKAN), was not present. Instead, bilateral hyperintensity and swelling of caudate nucleus, putamen, and thalamus were found. In addition, our patients showed a small corpus callosum and frontotemporal and parietal white matter changes, expanding the brain phenotype of patients with CoPAN. Metabolic investigations showed increased free carnitine and decreased acylcarnitines in the patientś dried blood samples. Carnitine palmitoyl transferase 1 (CPT1) deficiency was excluded by further enzymatic and metabolic investigations. As CoA and its derivate Acetyl‐CoA play an essential role in fatty acid metabolism, we assume that abnormal acylcarnitine profiles are a result of the COASY mutations. This report not only illustrates that WES is a powerful tool to elucidate the etiology of rare genetic diseases, but also identifies unique neuroimaging and metabolic findings that may be key features for an early diagnosis of CoPAN.